Youth and Advertisement on the Pages of Weekly Magazines Veja and IstoÉ (1980 decade) - Rossato, Luciana (Revista Crítica Histórica, 2020)
The objective of this article is to discuss how ideas of youth were advertised by the printed media through publicity pieces during the 1980 decade in Brazil, a period marked by the political opening and the broadening of consumer markets. Documents analyzed are 30 publicity pieces published in the magazines Veja and IstoÉ throughout the studied decade. For this analysis, we resorted to Margulis and Uresti’s (1996); Abramo’s (1997) concept of youth, as well as the concept of consumption by Featherstone (1995), and the concept of means and mediations by Martin-Barbero (2008). From the analysis of publicity pieces it is possible to affirm that the selected magazines were aimed to a specific group of young people belonging to a certain social class, spreading a concept of youth and of being young connected to freedom and to a life marked by multiple possibilities and choices. This article is a result of the study entitled “The Press and the Youth: representations of youth published by the Brazilian press (1960-2000)” under a Fapesc grant.